The Effect of Training, Work Stress and Work Ability on Work Performance PT Mukti Mandiri Lestari. - FITRI REZEKI; Rahmat Hidayat (STIE Binaniaga, 2021)
Abstract.Human resources are very influential on work performances, because work performance is one of requirement, that have tobe owned by employees in order to produce good performances, and to achieve company goals. If the goal has been achieved, the employee will get an achievement from the company.This research aims to examine, verify and obtain results on how the influence of training, job stress and work ability on work performance.The results of this research indicated three things: (1) there is a positive and significant influence on the training of PT. Mukti mandiri Lestari. (2) there is a positive and significant effect on the work stress variable of PT Mukti Mandiri Lestari. (3) and there is a positive and significant effect on work ability.